TH3.2: Women's Empowerment in Migration Index: Conceptual Framework and Early Results from Bangladesh - Alvi, Muzna (International Food Policy Research Institute, 2022)
In this presentation we describe a conceptual framework, and key elements of a Women's Empowerment in Migration Index (WEMI) that aims to measure the multiple dimensions of agency, resources and achievements of female migrants. We build on CGIAR's large body of work in developing women's empowerment metrics. The WEMI tries to unpack empowerment along the entire migration pathway looking at women's decision making about migration and work, control over assets and income, attitude towards employer violence, access to social networks, access to training and various aspects of self-efficacy and mental health as a migrant. We supplement this framework with data from a pilot survey with over 1000 returnee migrants in Bangladesh, in districts with high international out-migration of women to West Asian countries. The weighted average of the 3DE score for women in our sample is 0.60, out-of a possible maximum of 1. Of the 1018 returnee migrants surveyed, only 14 percent are found to be empowered using a cut-off score of 0.75. Of those women who were disempowered, mean adequacy score is 0.53, suggesting that they achieve adequacy in only 53 percent of the indicators. We believe that WEMI will be integral to monitoring progress towards SDG 8.7 on eradicating forced labor, modern slavery, and human trafficking.